Trade Protection in India: Economics vs. Politics? - Ira N. Gang; Mihir Pandey (Rutgers University, Department of Economics, 1996)
This paper investigates economic and political determinants of protection across the secondary (manufacturing) sector. Economic factors can be summarized by the infant industry argument and we expect industries which are relatively efficient compared to the rest-of-the-world to have low levels of protection. Moreover, the degree of protection should change as the relative efficiency of an industry changes over time. Political factors reflect pressure group politics: relatively inefficient industries may enjoy a great deal of protection because of political lobbying.
Keywords: D78; F13; O21; 330; Effective Rate of Protection; Liberalization; Political Economy; Protection; Trade